Construction of a ferroptosis-based prognostic model for breast cancer helps to discriminate high/low risk groups and treatment priority - Zhang, Liyong; Zhao, Tingting; Wu, Xiujuan; Tian, Hao; Gao, Pingping; Chen, Qingqiu; Chen, Ceshi; Zhang, Yi; Wang, Shushu; Qi, Xiaowei; Sun, Na (Frontiers in Immunology, 2023)
Breast cancer is one of the most common malignant tumors in the world with high morbidity and mortality. However, current multidisciplinary therapy does not save mortality from high-risk breast cancer metastases. Ferroptosis is a new regulated form of cell death. Ferroptosis is closely related to the occurrence and development of breast cancer, but the association between ferroptosis-related genes and breast cancer development and prognosis is unclear. Therefore, there is a need to better understand the relationship between breast cancer and ferroptosis. In our study, we downloaded the RNA-seq expression datasets and clinical samples datasets of breast cancer patients from public datasets and integrated immunity-and drug resistance-related data. Through a preliminary screening, 73 candidate ferroptosis factors were identified. The 12 genes were screened from the initial 73 candidate genes using univariate Cox regression analysis. The 12 genes were further analyzed by LASSO Cox regression analysis, and constructed a breast cancer prognostic risk prediction model containing 10 ferroptosis-related genes. And this model was characterized by the infiltration of immune cells. Furthermore, we validated the expression levels of ferroptosis-related genes in human breast cancer cell lines, and performed immunohistochemical (IHC) analysis of ferroptosis-related protein expression in cancer specimens. Based on the above results, this study provides a novel prognostic model for predicting the prognostic value of ferroptosis-related genes in breast cancer.